Expression, Clinical Significance, and Functional Prediction of MNX1 in Breast Cancer - Tian Tian; Meng Wang; Yuyao Zhu; Wenge Zhu; Tielin Yang; Hongtao Li; Shuai Lin; Cong Dai; Yujiao Deng; Dingli Song; Na Li; Zhen Zhai; et al. (Elsevier, 2018)
Motor neuron and pancreas homeobox 1 (MNX1) is a key developmental gene. Previous studies found that it was upregulated in several tumors, but its role in breast cancer (BC) remains unclear. In order to have a better understanding of this gene in BC, we examined the expression of MNX1 in BC tissues and normal breast tissues by qRT-PCR and by analyzing data from The Cancer Genome Atlas (TCGA) database. We also assessed the association of MNX1 expression with BC clinicopathological features and investigated the impact of MNX1 on BC survival. Potential molecular function of MNX1 was predicted through protein-protein interactions and functional enrichment. The results showed that the expression of MNX1 was significantly increased in BC tissues, especially in the HER2-positive subtype, and MNX1 expression was associated with several clinical characteristics, including menopause status, receptor status, subtypes, tumor size, lymph node metastasis, and race. In addition, patients with higher MNX1 expression had poorer survival. Enrichment analysis suggested that MNX1 is probably involved in biological processes and pathways related to nuclear division, cell cycle, and p53 signaling. In conclusion, our study suggests that MNX1 may act as a tumor promoter in BC. We hope these findings will draw more attention to MNX1 in future cancer studies. Keywords: motor neuron and pancreas homeobox 1, MNX1, breast cancer, clinical, expression, prognosis